The Implementation of Skills LearningMassage on Blin Students at Special School B Karangpawitan - Astri Ayu Irawan; Tedi Purbangkara (Universitas Muhammadiyah Enrekang, 2023)
This research aims to describe the implementation of skills learning massage on blind students at Special School C Karangpawitan. Research focuses on preparation, process and evaluation of learning. The type of research is descriptive. Research subjects included two students and a teacher as informants. Data was collected by observation, interviews and documentation. Data analysis uses descriptive-qualitative analysis. The research results show that the implementation of skills learning massage consisting of: 1) learning preparation including the teacher determining learning objectives and materials, as well as preparing learning equipment; 2) learning process: a) preliminary activities include the teacher conveying apperception and learning objectives, b) core activities consist of delivering material accompanied by giving examples of manipulation techniques, teaching techniques begins by directing students to wash their hands, saying the position masseur towards patients, guiding students to use learning equipment, and teaching techniques by holding and directing students, c) closing activities include ereview material, practice, and questions and answers; 3) learning evaluation is carried out through observation of student skills and oral tests.